2007
DOI: 10.1002/cne.21268
|View full text |Cite
|
Sign up to set email alerts
|

Decreased neurogenesis in aged rats results from loss of granule cell precursors without lengthening of the cell cycle

Abstract: It is well established that neurogenesis in the dentate gyrus slows with aging, but it is unclear whether this change is due to slowing of the cell cycle, as occurs during development, or to loss of precursor cells. In the current study, we find that the cell cycle time of granule cell precursors in middle-aged male rats is not significantly different from that in young adults. The size of the precursor pool, however, was 3-4 times smaller in the middle-aged rats, as determined using both cumulative bromodeoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
104
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 33 publications
11
104
4
Order By: Relevance
“…The density of Ki67 + and DCX + cells was lower in middle aged and older rats than in young adults, as shown previously (15)(16)(17)(18). Recent evidence indicates that the aging-related decrease in neurogenesis results from decreased proliferation, rather than changes in survival or cell cycle length (17,44). Regardless of the mechanism(s) of changes in normal aging, our results reveal that advanced age is an important modifier of the effects of radiation on the neurogenic population.…”
Section: Discussionsupporting
confidence: 85%
“…The density of Ki67 + and DCX + cells was lower in middle aged and older rats than in young adults, as shown previously (15)(16)(17)(18). Recent evidence indicates that the aging-related decrease in neurogenesis results from decreased proliferation, rather than changes in survival or cell cycle length (17,44). Regardless of the mechanism(s) of changes in normal aging, our results reveal that advanced age is an important modifier of the effects of radiation on the neurogenic population.…”
Section: Discussionsupporting
confidence: 85%
“…This finding is surprising in the light of earlier observations in rat models that a dramatic decline in the proliferation of NSCs occurs in the DG between young and old age (Olariu et al 2007;Rao et al 2006), but NSC numbers are preserved in the SGZ during the course of aging (Hattiangady and Shetty 2008). Furthermore, most studies on rodent models point out that proliferation of far fewer NSCs in the aged DG underlies the age-related reduction in net hippocampal neurogenesis (Cameron and McKay 1999;Hattiangady and Shetty 2008;Heine et al 2004;Kuhn et al 1996;McDonald and Wojtowicz 2005;Rao et al 2005;Seki and Arai 1995;Walter et al 2011but see Encinas et al 2011.…”
Section: Discussionmentioning
confidence: 87%
“…Multiple studies have shown that age-related decrease in neurogenesis is a result of proliferation of far fewer NSCs in the SGZ (Hattiangady and Shetty 2008;Kuhn et al 1996;Nacher et al 2003;Olariu et al 2007;Rao et al 2005Rao et al , 2006. Examination of the putative NSCs using markers such as Sox-2, GFAP, and vimentin over the course of aging has revealed no changes in NSC numbers in the rodent SGZ with aging (Aizawa et al 2011; however, see Encinas et al 2011;Hattiangady and Shetty 2008).…”
mentioning
confidence: 99%
“…Alternatively, as breeders in the present study were older on average than subordinates, the status differences observed may be a function of age. Though a regression of age on DCX expression within breeders was not significant, future studies should clarify whether low neurogenesis among breeders can be attributed to declines in neurogenesis with advancing age (Kuhn et al, 1996;Kempermann et al, 1998;Gould et al, 1999;Enwere et al, 2004;Barker et al, 2005;McDonald and Wojtowicz, 2005;Rao et al, 2005;Olariu et al, 2007;Ben Abdallah et al, 2010;Knoth et al, 2010), impaired negative feedback control of GCs (Sapolsky et al, 2002), or an age-related increase in neurogenic vulnerability to psychosocial stress (Simon et al, 2005).…”
mentioning
confidence: 99%